2011
DOI: 10.1590/s1516-35982011001000015
|View full text |Cite
|
Sign up to set email alerts
|

Digestible lysine for 63 to 103 day-old barrows of genetic lines selected for lean deposition

Abstract: -Ninety-six barrows from 63 to 103 days of age were used to evaluate the effects of dietary digestible lysine levels on performance and carcass traits of two genetic lines selected for lean deposition. Pigs with initial body weight of 23.800 ± 1.075 kg were allotted in a completely randomized block design, within a 4 × 2 factorial arrangement (four digestible lysine levels: 0.80, 0.90, 1.00, 1.10%, and two genetic lines), with six replicates and two pigs per experimental unit. There was no interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
0
4
0
6
Order By: Relevance
“…Studies conducted on finishing pigs fed with deficient diets or ajusted to the lysine requirement and containing 3.4 Mcal/ kg of EM have also shown that there is no effect of dietary lysine level on DFI and DWG (12). Even in growing pigs, fed with lower energy density diets, the effect of lysine on the productive performance has not been observed (3,23). According to those reported by several authors (4,12,13,23,24), the DFI is a variable that generally is not affected by the content of lysine in the diet, response that is observed when the diets are isocaloric and the daily intake of lysine increases linearly with the content of lysine in the diet, such as in the case of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted on finishing pigs fed with deficient diets or ajusted to the lysine requirement and containing 3.4 Mcal/ kg of EM have also shown that there is no effect of dietary lysine level on DFI and DWG (12). Even in growing pigs, fed with lower energy density diets, the effect of lysine on the productive performance has not been observed (3,23). According to those reported by several authors (4,12,13,23,24), the DFI is a variable that generally is not affected by the content of lysine in the diet, response that is observed when the diets are isocaloric and the daily intake of lysine increases linearly with the content of lysine in the diet, such as in the case of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Además, la cantidad de un aminoácido y la densidad energética en esas dietas determinan la deposición de proteína y grasa en la canal porcina (2). La lisina es el primer aminoácido limitante en dietas para cerdos, y se utiliza como referencia en la formulación considerando los valores recomendados de lisina digestible estandarizada para estimar los requerimientos de los otros aminoácidos esenciales y garantizar un óptimo crecimiento y rendimiento en carne magra (3)(4)(5). Se recomienda 0.52% de lisina digestible en la dieta de cerdos en etapa de finalización entre 80 y 120 kg de peso (6).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Para maximizar a deposição de carne na carcaça são necessárias dietas devidamente balanceadas em aminoácidos (Fortes et al, 2011). Dentre os aminoácidos, o teor de lisina digestível é considerado referência em dietas a base de milho e farelo de soja para avaliação do desempenho de suínos destinados ao abate.…”
Section: Introductionunclassified
“…A maioria das pesquisas desenvolvidas para avaliar o efeito de planos de nutrição utilizam animais do mesmo sexo como machos castrados (Souza Filho et al, 2000;Fortes et al, 2011), fêmeas (Kill et al, 2003) ou machos imunocastrados (Kiefer et al, 2011). Porém na prática, observa-se que várias granjas comerciais adotam a criação dos suínos em lotes mistos de machos castrados e fêmeas.…”
Section: Introductionunclassified